The Effectiveness of Repeated Shoot Tip Culture on Pathogens Load Reduction in Different Local Potato Genotypes in Malawi - J A, Nyaika; J P, Njoloma; S, Zimba; W F, Mwase; M F, Maliro; J M, Bokosi; M B, Kwapata (The International Journal of Biotechnology, 2014)
Potato production in Malawi still remains low, estimated at 11t/ha as compared to the potential 40t/ha due to disease infection resulting from seed recycling. Shoot tip culture in vitro is one of the tissue culture techniques that can potentially eliminate pathogens from infected plantlets. A study was therefore carried out to evaluate the effectiveness of repeated shoot tip culture on pathogen load reduction of some selected local potato genotypes grown in Malawi. A factorial experiment was laid out in a Completely Randomized Design (CRD) in which five genotypes including Magalabada, Rosita, Simoki, Usiwawatha and Violet were evaluated. Results showed that the mother stock tubers for all genotypes were infected with multiple pathogens at different incidences and intensities. PVY had an incidence of 100% with a low intensity in all genotypes. PVX had an incidence of 100% in Rosita and Magalabada, 80% in Usiwawatha and Violet and 60% in Simoki and their intensity was very high. The incidence for PVM was 80% in Usiwawatha, 60% in Violet, 10% in Rosita and Magalabada and 3% in Simoki; and their intensity was high. The incidence for PVS was 60% for Rosita, Magalabada and Usiwawatha, 18% for Violet and 10% for simoki; with a very high intensity. PVA incidence was 100% for Usiwawatha, 60% for Violet, 18% for Rosita and Simoki, and 5% for Magalabada; with a very low intensity. PLRV incidence was 10% for all genotypes and had a very low intensity. Traces of Bacterial wilt in low intensities were detected. Potato plantlets obtained after repeated sub-culturing of over six times resulted in reduced pathogen load at (P≤0.05) for the different pathogens. The chance of reducing the pathogen load in the different genotypes was relatively high at (P≤0.05).